PERENCANAAN BISNIS TERHADAP PERUSAHAAN - Muhamad Dzaki Hafidz Alfikry; Eloh Bahiroh (Jurnal Cakrawala Ilmiah, 2022)
Along with the development of business, competition also develops with the times. Some companies collapse, and others rise to dominate the market. Innovation and intense competition force the company to work hard to maintain its position. One of the keys to business success is the ability to incorporate innovative and creative ideas of high economic and commercial value into a mature and realistic business plan. Regardless of the type of business we run, Particularly if these ideas are then written down and communicated to other parties. A business plan is a blueprint for what to do with the business in the future, including allocating resources, paying attention to key factors, and addressing existing problems and opportunities. In general, the content of a business plan begins with a summary, mission statement, key factors, market analysis, production, management, and financial analysis such as break-even analysis and others.